2014
DOI: 10.1142/s0218126614500078
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Ultrasonic Preamplifier Noise Voltage Density

Abstract: Analysis of the noise voltage density evaluation procedures of the ultrasonic preamplifier is presented. Ultrasonic testing is demanding low noise reception channel. Techniques and equipment for ultrasonic preamplifier's noise performance evaluation are suggested. Equipment used and measurement technologies applied are described. One of the techniques suggested allows estimating the preamplifier noise with only impedance measurement results available. Sine wave correlation technique was used in the impedance m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The reflected and transmitted signals were amplified using a PA1008 preamplifier (AUT Solutions, US, TX). The preamplifier had a high voltage protection circuit, 1 kΩ input impedance [26]. An acquisition system of our own design [27] was used for data acquisition.…”
Section: Resultsmentioning
confidence: 99%
“…The reflected and transmitted signals were amplified using a PA1008 preamplifier (AUT Solutions, US, TX). The preamplifier had a high voltage protection circuit, 1 kΩ input impedance [26]. An acquisition system of our own design [27] was used for data acquisition.…”
Section: Resultsmentioning
confidence: 99%
“…Toneburst and CW sinusoid signals required fundamental frequency amplitude extraction. Sine wave correlation (SWC) technique [20] was used to extract the complex voltage V (VL or VH in (1), (2) accordingly)…”
Section: Output Impedance Measurement Systemmentioning
confidence: 99%
“…More details on amplifier, used in experiments, noise evaluation can be found in [20]. Operational amplifier LMH6624 was used as preamplifier.…”
Section: Sensitivity Analysis To Select Reference Loadsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to process the ultrasonic signal digitally is offering multiple advantages. In [24] it was shown that if expected electronics noise at reception channel output entotAout is 180 nV/Hz (output noise of AD8031 at minimum gain) then no more than 20 ps jitter clock is required to avoid the clock jitter noise influence. In order to make the quantization noise influence insignificant the resolution of ADC has to be above 9 bits at 100 MHz sampling frequency.…”
Section: Signal Digitization Electronicsmentioning
confidence: 99%